Математическая теория планирования эксперимента - Ермаков С. М. Сергей Михайлович; Бродский В. З. Вячеслав Зиновьевич; Жиглявский А. А. Анатолий Александрович; Козлов В. П. Виктор Павлович; Малютов М. Б. Михаил Борисович; Мелас В. Б. Вячеслав Борисович; Седунов Е. В. Евгений Витальевич; Федоров В. В. Валерий Вадимович (Справочная математическая библиотека)
Авторы указаны на обороте титульного листа.